Attached - Heller Rachel S.F; Levine Amir; Tarcherperigee (2010)
The writers guide readers in determining what attachment style they and their mate (or potential mate) follow, offering a road map for building stronger, more fulfilling connections with the people they love. The New Science of Adult Attachment, Decoding Relationship Behavior, Dependency is not a Bad Word, Your Relationship Toolkit and Deciphering Attachment Styles, The Three Attachment Styles in Everyday Life, Living with a Sixth Sense for Danger: The Anxious Attachment Style, Keeping Love at Arm's Length: The Avoidant Attachment Style, Getting Comfortably Close: The Secure Attachment Style, When Attachment Styles Clash, The Anxious - Avoidant Trap, Escaping the Anxious - Avoidant Trap: How the Anxious - Avoidant Couple Can Find Greater Security, When Abnormal Becomes the Norm: An Attachment Guide to Breaking Up, The Secure Way and Sharpening Your Relationship Skills, Effective Communication: Getting the Message Across, Working Things Out: Five Secure Principles for Dealing with Conflict, Epilogue, Acknowledgements, Bibliography, Index.